Reinforcement of nitrile rubber by in situ formed zinc disorbate (eXPRESS Polymer Letters)
Zinc disorbate (ZDS) was in situ formed by the reaction between sorbic acid (SA) and zinc oxide (ZnO) in nitrile rubber (NBR). The effects of SA amount on the curing characteristics, crosslink density and mechanical properties of peroxide- cured NBR were studied. The results showed that ZDS was generated mainly during the rubber vulcanization, rather than the open mill compounding phase. The results from the crosslink density determinations showed that the formation of ZDS significantly increased the ionic bond content in the vulcanizates. In addition, the formation of ZDS greatly enhanced the mechanical properties of NBR vulcanizates. The modulus, tensile strength, tear strength and hardness were found to be increased with the loading of ZDS. Preheating the compounds before compression moulding was beneficial to the formation of ZDS, and consequently the increases in mechanical properties. At 40 parts per hundred rubber (phr) of SA and 16 phr ZnO, five to six folds of tensile strength and tear strength of the neat NBR vulcanizate were achieved. Transmission electron microscopy (TEM) results confirmed the nano-dispersion structure of the polymerized ZDS in the NBR matrix.